2005
DOI: 10.1111/j.1467-9353.2005.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

The Doha Round of the World Trade Organization and Agricultural Markets Liberalization: Impacts on Developing Economies

Abstract: We investigate the impacts of multilateral removal of all border taxes and farm programs and their distortions on developing economies, using a world agriculture partial equilibrium model. We quantify changes in prices, trade flows, and production locations. Border measures and farm programs both affect world trade, but trade barriers have the largest impact. Following removal, trade expansion is substantial for most commodities, especially dairy, meats, and vegetable oils. Net agricultural and food exporters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…Milk supply equations are driven by expected net returns, which are driven by applicable federal or state policy. Demand equations are specified as a function of price, relevant substitute product prices and consumer income for various milk products (Johnson et al, 1993;Westhoff and Brown, 1999;Blayney and Normile, 2004;Fabiosa et al, 2005). These dairy cattle population projections (Supplementary Table S4) have an average annual decline rate of 0.32%, which agrees with CARB estimates of 0.5% decline in dairy cattle population from 2017 onward (CARB, 2022c).…”
Section: Scenario Analysis Of Methane Emissions From California Dairy...supporting
confidence: 52%
“…Milk supply equations are driven by expected net returns, which are driven by applicable federal or state policy. Demand equations are specified as a function of price, relevant substitute product prices and consumer income for various milk products (Johnson et al, 1993;Westhoff and Brown, 1999;Blayney and Normile, 2004;Fabiosa et al, 2005). These dairy cattle population projections (Supplementary Table S4) have an average annual decline rate of 0.32%, which agrees with CARB estimates of 0.5% decline in dairy cattle population from 2017 onward (CARB, 2022c).…”
Section: Scenario Analysis Of Methane Emissions From California Dairy...supporting
confidence: 52%
“…However, these studies have not really dealt with the effect of multilateral trade liberalization on trade flows. Some other studies (Fabiosa et al, 2005;Hoekman and Nicita, 2010;Decreux, and Fontagné, 2006;Deb and Al Amin, 2011) have looked at the effect of the WTO's Doha Development Round (which was launched in 2001) on trade flows, including by using the general equilibrium models, and tend to report a positive effect on exports. However, those studies have not looked systemically at the effect of multilateral trade liberalization on trade flows, although the RIBS 29,2 conclusion of the Doha Development Round could rightly be considered as a multilateral trade liberalization.…”
Section: Introductionmentioning
confidence: 99%
“…This results in an increase in agricultural income. On the other hand, Fabiosa et al (2005) concluded that net importing countries will feel the negative impacts of increasing agricultural prices. This was the reality in several food importing countries during the high food prices in 2008 (FAO 2008).…”
Section: Discussionmentioning
confidence: 99%